Mathematical-physical description of the oxygen-inhibited layer (OIL) in nanofilled dental polymers = Descripción físico-matemática de la capa inhibida por oxígeno en polímeros dentales nano rellenados - Ferreto Gutiérrez, Isabel 1974-
This research evaluates the presence of the oxygen-inhibited layer (OIL) on the top surface of a photopolymerized dental composite resin protected with a glycerin layer. This evaluation was conducted using physical and mathematical methods. Polymerized discs were fabricated to evaluate Vickers microhardness (VHN), and pre-and post-polymerized samples were used for the calculation of C-O/C-H ratios through Fourier Transform Infrared Spectroscopy (FTIR) (n=10), using two types of glycerin, one for medical use (MG) and another for dental use (DG). Surface hardness decreased from MG to DG to CO, and the increase in C-O/C-H ratios decreased in the same order (p<0.05). Samples protected with medical and dental glycerin layers are harder and exhibit lower C-O/C-H bond ratios than the control group.